시설재배 쑥갓 및 피망의 작물특성에 따른 Boscalid 및 Spinetoram의 잔류량 감소추이 - 황은진; Eun-jin Hwang; 박정은; Jung-eun Park; 도정아; Jung-ah Do; 정형욱; Hyung-wook Chung; 장희라; Hee-ra Chang (Hanguk hwangyeong nonghak hoeji, 2017)
BACKGROUND: This study was performed to evaluate the residue dissipation of boscalid and spinetoramon crown daisy and sweet pepper affected by the morphology of the crop. The half-lives and dissipation rate constants for boscalid and spinetoram on crown daisy and sweet pepper were calculated. And then lower limit of 95% confidence interval for dissipation rate constant could be used to propose the pre-harvest residue limit. METHODS AND RESULTS: The pesticide products diluted according to the pesticide label were applied one time on crown daisy and sweet pepper at 2 field sites, respectively. Initial concentration of boscalid and spinetoram on crown daisy after application were in the range of 72.80~117.15 mg/kg and 2.82~4.67 mg/kg, respectively. And Initial concentration of boscalid and spinetoramon sweet pepperwere in the range of 1.58~1.62 mg/kg and 0.10~0.21 mg/kg, respectively. Boscalid and spinetoram for crown daisy dissipted below the maximum residue limit(MRL) at 10 and 2 days after application, respectively. All residues concentration of boscalid and spinetoram for sweet pepper below theMRL at 0 day after application. The half-lives based on dissipation rate constant for boscalid and spinetoram on crown daisy were 4.2~4.9 days and 3.0~2.4 days respectively. And the half-lives for boscalid and spinetoram on sweet pepperwere 6.7~7.0 days and 2.8~4.0 days respectively. CONCLUSION: The difference in initial concentration of boscalid and spinetoram among crop commodities were due to different cropmorphology with larger surface areas. This study was suggested that pre-harvest residue limit would be calculated from lower limit of 95% confidence interval for dissipation rate constant andwould be useful to protect consumers by controlling the pesticide residues in crop.